Representation of Social Actors of The Press Statement of The President of Indonesia in The Issue of Covid-19 Pandemic - Suswanto Ismadi Megah (Universitas Veteran Bangun Nusantara, 2020)
This research was aimed to identify the social actors represented in the press statement of the President of Indonesia in the issue of covid-19 pandemic using two analytical models of Halliday's transitivity model (Halliday & Matthiessen, 2004) and Van Leeuwen’s (1996) framework applied to analyze the clauses were counted and analyzed critically through public discursive models. The research data were obtained from two news published by Setkab.go,id (Secretary of cabinets).. The results showed show the positive portrayal or inclination of the press statement towards one social actor and it also portrays the ideology or stance of the president shown inclination towards as a current ruler of government at time of data collection and his influence on Setkab.go.id. he showed that actor in material process represented in the role allocation of government was aimed to show the action of the Indonesian President toward the issue of the covid-19 pandemics.Keywords: social actors, Transitivity and President’s Press Statement